ASSESSMENT OF ESTHETIC SMILE COMPONENTS BY DENTAL STUDENTS - Demirekin, Zeynep Basagaoglu; Buyukcavus, Muhammed Hilmi (International Journal of Research -GRANTHAALAYAH, 2023)
Background: The present information indicates that most students utilized the technology-based system well, but they missed some practical activities. Assessment of students’ satisfaction with the e-learning activities and asking for feedback can help institutions to improve the know-how about e-learning practices. Hopefully, the sudden pandemic-related shift through modes of education will not be considered an unfavorable impact on education but an evolving experience to pave a comprehensive way to technology-based educational activities. Material and methods: The study was performed on 580 dental students. Among the eight components of the balanced smile, six factors (the smile arc, smile line, dark buccal corridors, gingival margin and incisal edge asymmetries, tooth axis, and dental midline inclinations) apart from those related to dental and gingival ones, were examined on photographs. Manipulations were made on the photo of a female patient with the ideal smile. Results: Statistically significant differences were observed between the preclinical and clinical groups and, in binary comparisons, between curricular years at pre-clinical and clinical levels (P < 0.05). Conclusions: Our findings confirm the reports from previous investigations considering the impact of dental education on dental students’ perception of dentofacial esthetics.